Gestión de la información territorial municipal a través del catastro multifinalitario (Estudios) - Erba, Diego (2017)
The first territorial land was implemented in Latin America in 1824. Since then, and during the rest of the nineteenth century, 8 countries created public institutions with functions related to real estate advertising, while the other 11 countries began to work their land information only from the twentieth century. In most countries of the region cadastral systems they were born structured (and continue to develop) under the basic model that only includes economic data, land value and improvements; physical, shape, dimensions and location of the property; and legal, owners and holders.